Ain't I an anthropologist : Zora Neale Hurston beyond the literary icon - Freeman Marshall, Jennifer L., 1968- (Urbana : University of Illinois Press, 2023)
"Iconic as a novelist and popular cultural figure, Zora Neale Hurston remains underappreciated as an anthropologist. Is it inevitable that Hurston's literary authority should eclipse her anthropological authority? If not, what sociocultural and institutional values and processes shape the different ways we read her work? Jennifer L. Freeman Marshall considers the polar receptions to two of Hurston's areas of achievement by examining the critical response to her work across both fields. Drawing on a wide range of readings, Freeman Marshall explores Hurston's popular appeal as iconography, her elevation into the literary canon, her concurrent marginalization in anthropology despite her significant contributions, and her place within constructions of Black feminist literary traditions. Perceptive and original, Ain't I an Anthropologist is a long-awaited reassessment of Zora Neale Hurston's place in American cultural and intellectual life"--
Introduction: "Twice as Much Praise or Twice as Much Blame" -- On Firsts, Foremothers, and "The Walker Effect" -- Signifying "Texts": The Race for Hurston -- Deconstructing an Icon: Tradition and Authority" -- Ain't I an Anthropologist? -- "Mules and Men: "Negro folklore . . . is still in the making" -- "Burning spots": Reading Tell My Horse -- Epilogue: On Icons, Interdisciplines, and Communities
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 21, 2023).
eBooks on EBSCOhost
Keywords: Hurston, Zora Neale -- Criticism and interpretation; Hurston, Zora Neale -- Knowledge and learning; Hurston, Zora Neale; Anthropology; Anthropologie; anthropology; SOCIAL SCIENCE / Ethnic Studies / American / African American & Black Studies; LITERARY CRITICISM / American / African American & Black; SOCIAL SCIENCE / General; Anthropology; Learning and scholarship; Electronic books; Criticism, interpretation, etc